Human DDX56 protein interacts with influenza A virus NS1 protein and stimulates the virus replication - TURAN, KADİR (SOC BRASIL GENETICA, 2021)
Influenza A viruses (IAV) are enveloped viruses carrying a single-stranded negative-sense RNA genome. Detection of host proteins having a relationship with IAV and revealing of the role of these proteins in the viral replication are of great importance in keeping IAV infections under control. Consequently, the importance of human DDX56, which is determined to be associated with a viral NS1 with a yeast two-hybrid assay, was investigated for IAV replication. The viral replication in knocked down cells for the DDX56 gene was evaluated. The NS1 was co-precipitated with the DDX56 protein in lysates of cells transiently expressing DDX56 and NS1 or infected with the viruses, showing that NS1 and DDX56 interact in mammalian cells. Viral NS1 showed a tendency to co-localize with DDX56 in the cells, transiently expressing both of these proteins, which supports the IP and two-hybrid assays results. The data obtained with in silico predictions supported the in vitro protein interaction results. The viral replication was significantly reduced in the DDX56-knockdown cells comparing with that in the control cells. In conclusion, human DDX56 protein interacts with the IAV NS1 protein in both yeast and mammalian cells and has a positive regulatory effect on IAV replication. However, the mechanism of DDX56 on IAV replication requires further elucidation.
Keywords: Influenza A viruses; NS1 protein; RNA helicase DDX56; virus-host interaction; NUCLEOLAR HELICASE DDX56; TRANSLATION INITIATION; RNA-BINDING; DOMAIN; TRANSCRIPTION; POLYMERASE; EXPRESSION; APOPTOSIS; SELECTION; SERVER